Continuous g-C3N4 layer-coated porous TiO2 fibers with enhanced photocatalytic activity toward H2 evolution and dye degradation. Issue 17 (1st April 2022) - Liu, Jing; Zheng, Jinxiao; Yue, Guichu; Li, Huaike; Liu, Zhaoyue; Zhao, Yong; Wang, Nü; Sun, Chenghua; Cui, Zhimin
Abstract : TiO2 @g-C3 N4 core/shell fibers with a continuous g-C3 N4 layer packing around exhibit high photocatalytic efficiency toward H2 production and RhB degradation due to the intimate core/shell structure with a high-quality TiO2 /g-C3 N4 heterojunction. Abstract : TiO2 /g-C3 N4 composite photocatalysts with various merits, including low-cost, non-toxic, and environment friendliness, have potential application for producing clean energy and removing organic pollutants to deal with the global energy shortage and environmental contamination. Coating a continuous g-C3 N4 layer on TiO2 fibers to form a core/shell structure that could improve the separation and transit efficiency of photo-induced carriers in photocatalytic reactions is still a challenge. In this work, porous TiO2 (P-TiO2 )@g-C3 N4 fibers were prepared by a hard template-assisted electrospinning method together with the g-C3 N4 precursor in an immersing and calcination process. The continuous g-C3 N4 layer was fully packed around the P-TiO2 fibers tightly to form a TiO2 @g-C3 N4 core/shell composite with a strong TiO2 /g-C3 N4 heterojunction, which greatly enhanced the separation efficiency of photo-induced electrons and holes. Moreover, the great length–diameter ratio configuration of the fiber catalyst was favorable for the recycling of the catalyst. The P-TiO2 @g-C3 N4 core/shell composite exhibited a significantly enhanced photocatalytic performance both in H2 generation and dye degradation reactions under visible light irradiation, owing to the specific P-TiO2 @g-C3 N4 core/shell structure and the high-quality TiO2 /g-C3 N4 heterojunction in the photocatalyst. This work offers a promising strategy to produce photocatalysts with high efficiency in visible light through a rational structure design.